(3ZGjI GdeCehd aj TQM RHOI GdCUhds - (3GdHZOGOj, GdLhGO GdHZOGOj, LhGO Hf SYO (B((3SYjO(B) (3Hf LhGO GdHZOGOj, J (B1065(3g` (B1655(3es
(3ChdgG (B:s
(3ChdgG(B: (3fMeOc jG ef habfG dSdhc WQjb GdYed HcJGHg GdeHjf (B... (3bGd (B.. (3HYO GdNWHI(B: (3QJHJgG Ydi NeSI efGgL, Cbhd(B: (3QJHJ (B..s
(3BNQgG (B:s
(3BNQgG(B: (3aeG cGf Cbhi aj Xfg jLH GdYed Hg (B... (3aEf Pdc gh GdChdi Hd WQjb GdfLGI aj GdBNQI hGdChdi, fLGfG Gddg hEjGce ef YbhHGJg hCUHZ YdjfG hEjGce ef Yeje aVdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 142s
(3GdPQjYI, L (B16: 13s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs